2020
DOI: 10.1002/ceat.202000051
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon by Potassium Carbonate Activation from Pine Sawdust (Pinusmontezumae Lamb.)

Abstract: Activated carbon (AC) was gained from Pinus montezumae (PM) wood sawdust and chemical activation with K2CO3 was used for obtaining activated carbons. Variations in reaction conditions such as temperature, impregnation ratio (IR), and activation time were carried out to study their influence on the specific surface area (SSA) and average pore volume (APV) in AC. Materials were analyzed by means of Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and X‐ray diffraction (XRD) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 44 publications
4
16
0
Order By: Relevance
“…It can be observed that the iodine number increased from 627.03 to 892.31 mg/g with increasing the carbonization time from 0.5 to 1 h. As the contact time between Silver berry seeds and ZnCl 2 increases up to 1 h, a decrease in the iodine number was observed, indicating that a longer duration of carbonization time caused the collapse of micropores walls and recombination of carbon atoms. [47] Similar results have been reported by Yorgun et al, Altintig & Kirkil, and Sayğılı & Güzel. [8,14,39] On the other hand, the percentage of yield decreased with increasing time of carbonization, which was due to the increase in the carbon burn-off.…”
Section: Optimization Of Gac Synthesis Conditionssupporting
confidence: 83%
“…It can be observed that the iodine number increased from 627.03 to 892.31 mg/g with increasing the carbonization time from 0.5 to 1 h. As the contact time between Silver berry seeds and ZnCl 2 increases up to 1 h, a decrease in the iodine number was observed, indicating that a longer duration of carbonization time caused the collapse of micropores walls and recombination of carbon atoms. [47] Similar results have been reported by Yorgun et al, Altintig & Kirkil, and Sayğılı & Güzel. [8,14,39] On the other hand, the percentage of yield decreased with increasing time of carbonization, which was due to the increase in the carbon burn-off.…”
Section: Optimization Of Gac Synthesis Conditionssupporting
confidence: 83%
“…In addition, the absorption peak of 2884-2899 cm À 1 was associated with the methyl and methylene groups (CÀ H) belonging to the olefin compounds. [39] The CÀ H bonds and its conjugates in the acyclic compound group were also identified at the absorption peak of 1623-1628 cm À 1 , confirming the aliphatic properties in the activated carbon samples. Subsequently, the primary amine bond was found in the absorption bands of 2423 and 2419 within the MOAC and MOAC-H 3 PO 4 samples, respectively.…”
Section: Materials Analysesmentioning
confidence: 66%
“…XRD pattern of the MOAC monolith samples showed a low peak at 24-26°angle which correlated with the reflection plane (002), indicating a low graphite crystalline degree towards good amorphous properties. [39,40] Furthermore, a broad peak was found at an angle of 42-45°, which correlated to the reflection plane (100), therefore, indicating the disturbed (turbostratic) interlayer graphite carbon. [41] This is speculated relatively high electrical conductivity to improve the electrochemical properties.…”
Section: Materials Analysesmentioning
confidence: 93%
“…Potato skins have almost the same chemical content as the fruit, which has 30% -40% cellulose which can produce carbon when heated to high temperatures. The addition of several chemical reagents in the processing of carbon electrodes can be used, such as ZnCl2, KOH, NaOH, K2CO3, H2SO4, H3PO4, and HNO3 [16][17][18]. ZnCl2 activator was seleced as chemical reagent this study due to their characteristics as a dehydrating agent, can evaporate completely at a temperature of 756 °C thus intiated optimum micropores [19].…”
Section: Introductionmentioning
confidence: 99%